2012
DOI: 10.1007/s10532-012-9591-4
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-mediated bioaugmentation of sequencing batch reactors for enhancement of 2,4-dichlorophenoxyacetic acid removal in wastewater using plasmid pJP4

Abstract: Plasmid-mediated bioaugmentation was demonstrated using sequencing batch reactors (SBRs) for enhancing 2,4-dichlorophenoxyacetic acid (2,4-D) removal by introducing Cupriavidus necator JMP134 and Escherichia coli HB101 harboring 2,4-D-degrading plasmid pJP4. C. necator JMP134(pJP4) can mineralize and grow on 2,4-D, while E. coli HB101(pJP4) cannot assimilate 2,4-D because it lacks the chromosomal genes to degrade the intermediates. The SBR with C. necator JMP134(pJP4) showed 100 % removal against 200 mg/l of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“… Inoue et al (2012) concluded that genetic bioaugmentation with P. putida and E. coli cells harboring plasmid pJP4 can stimulate the degradation of 2,4-D in soil without a substantial impact on the soil microbial community, as reflected by the values of parameters which provide information on carbon source utilization (through the use of the well-known Biolog TM plates) and nitrogen transformations (nitrate reduction assay, quantification of amoA gene of ammonia-oxidizing bacteria, quantification of nirK and nirS genes of denitrifying bacteria). In sequencing batch reactors, Tsutsui et al (2013) achieved a complete degradation of 2,4-D by plasmid (pJP4)-mediated bioaugmentation with Cupriavidus necator JMP134 and E . coli HB101 as donor strains.…”
Section: Genetic (Plasmid-mediated) Bioaugmentationmentioning
confidence: 99%
“… Inoue et al (2012) concluded that genetic bioaugmentation with P. putida and E. coli cells harboring plasmid pJP4 can stimulate the degradation of 2,4-D in soil without a substantial impact on the soil microbial community, as reflected by the values of parameters which provide information on carbon source utilization (through the use of the well-known Biolog TM plates) and nitrogen transformations (nitrate reduction assay, quantification of amoA gene of ammonia-oxidizing bacteria, quantification of nirK and nirS genes of denitrifying bacteria). In sequencing batch reactors, Tsutsui et al (2013) achieved a complete degradation of 2,4-D by plasmid (pJP4)-mediated bioaugmentation with Cupriavidus necator JMP134 and E . coli HB101 as donor strains.…”
Section: Genetic (Plasmid-mediated) Bioaugmentationmentioning
confidence: 99%
“…It implied that pH also played an important role in its set-up. Besides, the initial pollutant concentration is also an important factor for the set-up of bioaugmentation system that concerned by various researchers [19][20][21][22]. Based on the analysis of its mechanisms, both inoculum and pH and pollutant load should be optimized for its application in engineering [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Many plasmid mediation bioaugmentation (genetic bioaugmentation) studies have been focused on the herbicide 2,4-D(Bathe et al, 2004b, Aspray et al, 2005, Quan et al, 2011, Newby et al, 2002, Tsutsui et al, 2013.Tstusui et al (2013) observed enhanced plasmid pJP4 mediated bioaugmentation using sequencing batch reactors for the removal of 2,4-D. Cupriavidus necator JMP134 and E. coli HB101 were used as plasmid donor strains. Complete removal of 2,4-D was achieved in the reactor with C. necator JMP134.…”
mentioning
confidence: 99%